The Impact of Diabetes Mellitus Gym for Controlling the Level of Blood Glucose (HbA1c) - Jain, Asrin; Mulidah, Siti; Fitriyani, Aris; Fitriyani, Walin (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes Mellitus (DM) is a chronic progressive disease. Based on Health Department of Republic Indonesia (2016) was reported that DM prevalence increase from 1,1% (2007) to 2,1% (2013). There are four aspects for controlling DM such as education, arrange of nutrition, practice, and drug compliance (Health Department of Republic Indonesia, 2016). This controlling is aim to increase the quality of life for DM patients. This study is aimed to know the impact of DM gym for controlling the level of blood glucose (HbA1c). Type of this study is an experimental study by static pretest and posttest with control groups design. Respondents of study were DM patients in area of Puskesmas II Sokaraja. The number of samples were 26 respondents. The measurement was done by using questioner and blood glucose check (HbA1c) for pre and posttest. The analysis was used t test. Majority of respondents were female, almost all of respondents educational were basic education (SD and SMP), majority of respondents were 35. 60 years old, majority of respondents were unemployed, and majority of respondents suffering from DM were in middle duration (1-5 years). DM gym can decrease the level of HbA1c for 1,79 mg/dl (p=0,00) from intervention group and 0,63 mg/dl (p=0,00) from control group. The analysis of t test show that DM gym can control the level of blood glucose (HbA1c) significantly (p=0,00). DM gym can control the level of blood glucose (HbA1c). Health staffs need to increase motivation of public in doing DM gym regularly.